Model-based predictive control of large-scale systems using a neural estimator - Tzafestas, Spyros G.; Kyriannakis, Efthimios; Anthopoulos, Yiannis (Zielona Góra: Uniwersytet Zielonogórski)
An approach to the design of discrete-time decentralized control systems based on model-based predictive control (MBPC) and neural estimation is proposed. The class of interconnected large-scale systems (LSS) is considered, and a model is used at each control station to predict the corresponding subsystem output over a long time period.
Keywords: sterowanie; sterowanie-teoria; sztuczna inteligencja; matematyka stosowana; informatyka